Private Participation in the Transport Sector : Lessons from Recent Experience in Europe and Central Asia - Cuttaree, V.; Humphreys, M.; Muzira, S.; Strand, J-P. (World Bank, Washington, DC, 2014)
This report was commissioned to draw lessons from the experiences with public private partnerships (PPPs) in the transport sector in Europe and Central Asia (ECA) countries. The report will review experiences to date with private participation in the transport sector with a primary focus on experiences in the ECA countries and Europe. To carefully prepare and select the most desirable PPP projects during the most severe economic downturn since the Second World War, availability of regional best practices would be helpful. This report will provide guidance for successful PPP implementation and will hopefully encourage public authorities to critically evaluate their project designs. The lessons from this study apply regardless of the financial crisis. While the dire economic environment will considerably impact the current PPP pipeline, the fundamental success factors for these projects will remain the same. During times of economic turmoil, evaluating past investment projects can provide lessons for stimulating the next period of economic growth. The report discusses the impact of the financial crisis separately in annex B.